Effect of Bacterial Chitinases on the Growth and Aflatoxin Production of flavus Link ex Fries and A. parasiticus Speare - Mozar-doyungan, Stella Marie; F. Dalmacio, Ida (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The ability of the crude hacterial chitinases produced from Bacillus circulans B1037 (5Bc), Arthrobacter luteus B1077 (6A1), B. circulans B1045 (7Bc), Streptomyces griseus B1562 (9Sg), Serratia marcescens LPC19 B1748 (11Sm) and S. marcescens LPM42 B1749 (14Sm) to inhibit growth and aflatoxin production of Aspergillus flavus and A. parasiticus was studied. Results show that the crude chitinases can control the growth of the two aflatoxigenic molds, A. favus and A. parasiticus in corn kernels as indicated by the significant reduc-tion in the number of infected kernels. In addition, aRatoxin B, was not detected in some-enzyme treated corn kernels previously infected with the test organisms.